Technical Notes: Determination of Manning Roughness Coefficient for PVC Gutters - Mas Mera; Rizki Robi (Jurnal Teknik Sipil, 2013)
Abstract. This study is about the determination of the Manning roughness coefficient for a PVC (Polyvinyl Chloride) gutter and of its capacity due to longitudinal-slope changes. Both the roughness coefficient and gutter slope are factors that greatly affect both the velocity and depth of flow in a channel. For this purpose, an experiment is performed in the laboratory using a PVC gutter with adjustable slopes. The Manning formula, i.e. a function of: flow rate; channel roughness coefficient; flow depth (wet cross-sectional geometries); and channel longitudinal-slope, is then used. Water is supplied by a pump, and the discharge flow rate is determined by collecting the water that comes out at the end of the gutter downstream using a bucket. Then, both the volume of water in  the bucket and the time it taking are measured. The flow depths are measured with a ruler (the other geometry sizes of the gutter are fixed, the length of 4m, width 12cm, height 10cm). These measurements were performed five times for each slope variation with 1cm/4m step (from 1cm/4m to 10cm/4m). The results show that the values of the Manning roughness coefficient for the PVC gutter range from 0.010 to 0.014. Due to an increase in the slope of 1cm/4m to 10cm/4m, the flow depth drops 60% to 40% for the same discharge. Abstrak. Penelitian ini adalah tentang penentuan koefisien kekasaran Manning talang PVC (Polyvinyl Chloride), dan penentuan kapasitas talang akibat perubahan kemiringan memanjang saluran. Koefisien kekasaran dan kemiringan memanjang dasar saluran merupakan dua faktor yang sangat berpengaruh terhadap kecepatan dan kedalaman aliran suatu saluran. Oleh karena itu, dilakukanlah percobaan di laboratorium menggunakan sebuah talang PVC yang kemiringannya dapat diatur. Rumus yang digunakan adalah rumus Manning yang merupakan fungsi dari kecepatan aliran, koefisien kekasaran saluran, kedalaman aliran (geometri penampang basah saluran), dan kemiringan memanjang saluran. Air dipasok oleh sebuah pompa, dan debit alirannya ditentukan dengan menampung air yang keluar di ujung hilir saluran dengan sebuah ember. Volume air ember dan lama waktu yang diperlukan diukur. Kedalaman aliran diukur dengan mistar (ukuran lain geometri saluran adalah tetap, yaitu panjang 4m, lebar 12cm, tinggi 10cm). Pengukuran dilakukan lima kali untuk setiap perubahan kemiringan memanjang saluran dengan tahapan kemiringan 1cm/4m (dari 1cm/4m sampai 10cm/4m). Hasil percobaan menunjukkan  nilainilai koefisien kekasaran Manning talang air PVC berkisar antara 0,010 sampai 0,014. Akibat peningkatan kemiringan dari 1cm/4m ke 10cm/4m, kedalaman aliran turun sampai 60% (tinggal 40%) untuk debit yang sama.